Embodiments of Shape: Cubes and Lines and Slender Gilded Thongs in Picasso, Duchamp and Robbe-Grillet - Emma Kafalenos (Studies in 20th & 21st Century Literature, 1990)
An account, from several perspectives, of a structural type exemplified by Pablo Picasso's Les Demoiselles d'Avignon (1907), generally considered the first Cubist painting; Marcel Duchamp's Nu descendant un escalier (1912), and Alain Robbe-Grillet's La Maison de rendez-vous (1965). To compare contemporary texts to paintings that arose in the moment immediately preceding the full achievement of the non-representational suggests that both incorporate trivial—and even popular—elements because they are so eminently cuttable. In each work, the decomposition of objects to their pieces shifts interest from paradigm to syntagm, while retaining sufficient reference to paradigm to embody syntagm, to make structure perceptible. All three are heterotopias, following Michel Foucault's terminology, in which the many spatio-temporal perspectives each portrays are assembled in a single structure, without the hierarchy that a unified perspective or a linear chronology can impose.
Keywords: perspectives; structures; Pablo Picasso; Les Demoiselles d' Avignon; Cubist painting; Marcel Duchamp; Nu descendant un escalier; Alain Robbe-Grillet; La Maison de rendez-vous; contemporary texts; painting; cubism; art; non-representational; trivial; popular; elements; cuttable; decomposition; object; objects; piece; pieces; paradigm; syntagm; structure; perceptible; heterotopias; Michel Foucault; terminology; spatio-temporal; perspective; portrays; single structure; hierarchy; linear chronology